1995
DOI: 10.1002/bem.2250160602
|View full text |Cite
|
Sign up to set email alerts
|

Biologic effects of prolonged exposure to ELF electromagnetic fields in rats: II. 50 Hz magnetic fields

Abstract: To provide possible laboratory support to health risk evaluation associated with long-term, low-intensity magnetic field exposure, 256 male albino rats and an equal number of control animals (initial age 12 weeks) were exposed 22 h/day to a 50 Hz magnetic flux density of 5 microT for 32 weeks (a total of about 5000 h). Hematology was studied from blood samples before exposure to the field and at 12 week intervals. Morphology and histology of liver, heart, mesenteric lymph nodes, and testes as well as brain neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 30 publications
1
16
1
Order By: Relevance
“…Sieron et al [2004] found daily exposure to 10 Hz fields at 1.8-3.8 mT increased synthesis of dopamine and 5-hydroxytryptamine in the frontal cortex of rats. No effects were seen, however, on the levels of these amines or on their metabolites with these fields, or using long-term exposure to 50 Hz fields at 5 mT [Margonato et al, 1995].…”
Section: Effects On Neurotransmitter Functioncontrasting
confidence: 57%
“…Sieron et al [2004] found daily exposure to 10 Hz fields at 1.8-3.8 mT increased synthesis of dopamine and 5-hydroxytryptamine in the frontal cortex of rats. No effects were seen, however, on the levels of these amines or on their metabolites with these fields, or using long-term exposure to 50 Hz fields at 5 mT [Margonato et al, 1995].…”
Section: Effects On Neurotransmitter Functioncontrasting
confidence: 57%
“…As reported in the literature, up to now four long-term carcinogenicity bioassays have been performed to assess the carcinogenic potential of 50-60 Hz MF on rats. [23][24][25][26] Altogether, the results of these studies did not show any carcinogenic effects from ELFMF. However, some doubts were raised in the scientific community concerning the design and conduct of those studies, with particular regard to the number of animals per group and sex, the starting of exposure at mature age and the duration of the experiments, which was no more than 110 weeks (equivalent to two thirds of the life of the animals), too short to identify rare pathological lesions in later life.…”
Section: Experiments On S-50 Hz Mf Alonesupporting
confidence: 53%
“…As reported in the literature, up to now four long‐term carcinogenicity bioassays have been performed to assess the carcinogenic potential of 50‐60 Hz MF on rats …”
Section: Introductionmentioning
confidence: 99%
“…Exposure to electric field appears to alter the secretion of neurotransmitters such as NE, DA, serotonin metabolite 5HIAA, HVA and DOPAC in the rat hypothalamus or striatum (Vasquez et al, 1988;Zecca et al, 1991), although some authors have been unable to confirm these findings (Margonato et al, 1995). Other studies, of species such as dairy cattle (Burchard et al, 1998) and macaques (Seegal et al, 1989), have found that exposure to electric fields alters the secretion of some neurotransmitters.…”
Section: Discussionmentioning
confidence: 91%